Cyclometallated 2‐Phenylpyrimidine Derived Platinum Complexes: Synthesis and Photophysical Properties. Issue 16 (14th April 2021) - Fecková, Michaela; Kahlal, Samia; Roisnel, Thierry; Saillard, Jean‐Yves; Boixel, Julien; Hruzd, Mariia; le Poul, Pascal; Gauthier, Sébastien; Robin‐le Guen, Françoise; Bureš, Filip; Achelle, Sylvain
Abstract: A series of five platinum (II) complexes based on 2‐phenylpyrimidine ligands have been designed. Pyridine and chloride were used as auxiliary ligands. These complexes exhibit a slightly distorted square‐planar geometry. The nature and position of substituent on the phenyl ring was thoroughly studied. The presence of an electron‐donating substituent on the phenyl ring in the para position of the platinum atom leads to a red shift of the lowest‐energy absorption band, which corresponds to the HOMO→LUMO transition and permits to obtain phosphorescence in deoxygenated CH2 Cl2 solution. All compounds are emissive in the solid state with a significant redshift for complexes bearing electron‐donating substituent on the phenyl ring of phenylpyrimidine ligand. Abstract : A series of 2‐phenylpyrimidine platinum (II) complexes were designed and their phosphorescence properties were studied. The presence of an electron donating group in para position of Pt atom on the phenyl ring significantly increased emission intensity in the solution and lead to a red‐shifted phosphorescence in the solid state.